ANALISIS PENILAIAN KINERJA KEUANGAN PERUSAHAAN TERHADAP KELAYAKAN MENDAPATKAN KREDIT MODAL KERJA - Ilham, Nurul Fadillah; S, Masnawaty; Nuraisyiah, Nuraisyiah (Jurnal Sains Riset, 2024)
This research aims to determine the performance assessment of prospective debtor companies regarding the feasibility of obtaining working capital credit by BRI KCP Pettarani. Data collection techniques were carried out by conducting interview techniques, documentation techniques and library techniques. The data analysis technique was carried out using qualitative data analysis, namely collecting the data needed in this research, through interviews and documentation. As well as quantitative data analysis using calculations using formulas in analyzing the compa|ny's financial performance and calculating the amount of credit given by the bank.The results of this research are the first benchmark for banks, in this case, checking the SLIK (Financial Information Service System) of prospective debtors. The basis for approval for granting credit is an analysis of financial reports. Reportn Profit and Loss Reportn Balance Sheet of the prospective debtor for the last 3 years as a component of the financial reportngan which is a consideration for the bank. In analyzing the financial reports of potential bank debtors, there are 4 financial ratios, namely Liquidity Ratio, Activity Ratio, Solvency Ratio and Profitability Ratio. The business has been running for at least 2 years and meets the criteria for measurement used by the bank, namely the company's performance which is taken into consideration by the bank in deciding whether or not it is appropriate to grant working capital credit. The principle that influences debtors is the principle of Character. The principle that is indicated as problematic for debtors is the Capital principle. The action taken by Bank to implement the principle of supervision is to carry out an inventory. The bad character of the debtor is an obstacle faced by banks in the credit granting process